THE EFFECT OF OVAPRIM AND hCGINJECTION WITH DIFFERENT DOSES ON FERTILIZATION, HATCHING RATE AND SURVIVAL RATE OF LARVAE OF CLIMBING PEARCH (ANABAS TESTUDINEUS - RAHAYU SIREGAR; SUKENDI SUKENDI; NETTI ARYANI (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRAC  The research was conducted fromMayto June 2017 in Fish Breeding and Hatchery Laboratory Faculty of Fisheries and Marine, University of Riau. The purpose of thisresearch was toevaluate the effect of ovaprim and hCG to ferilization, hatching rate, and survival rate of larvae of climbing pearch (anabas testudineus) fish. The treatment used in this research was in injection of ovaprim dan hCG with different doses is : P1: ovaprim 0,5 ml/kg body weight, P2: ovaprim 0,7 ml/kg body weight, P3: hCG 500 IU/kg body weight, P4:hCG 1000 IU/kg body weight and 1 ml of NaCl fis 0,9%0,2 ml of body weight. The result showed that ovaprim dose of 0,5 ml/kg of body weight was the bestin turn of fertilization 74%, hatching rate 75%, survival rate of larvae 74%. The temperature ranged from 27-28%ºC, pH was 5-7 and DO (Disolved oxygen) 3,97-5,22 ppm. Key word :Ovaprim, hCG, Fertilization, Hatching rate, Survival rate, Anabas testudineus